Comprehensive Management of Congenital Cataract in Dizygotic Twin Babies - Windya Tri Hapsari; Indri Wahyuni; Rozalina Loebis (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2021)
Introduction: One of the leading causes of infant blindness is cataract. The prevalence of congenital cataract has been estimated in the range between 1 and 15 per 10.000 children globally. Congenital cataract in twin babies is a rare case. This case will report the outcome of comprehensive management of congenital cataract in dizygotic twin babies. Case presentation: Eight months old dizygotic twin babies came to our clinic with the primary complaint of whitish appearance in the pupil of both eyes since birth. They were born aterm with cesarean delivery. The birth weight was 2.700 g and 3.100 g respectively. They were the fourth and fifth children in the family. There was no family history of congenital cataract. The visual acuity of both eyes was positive response to light stimuli. The cataract was bilateral and dense on both babies. Fundus reflex and TORCH examinations were negative. Ultrasonography (USG) of the retina was normal on both babies. Conclusions: Isolated congenital cataract in twin babies is an unusual condition that should be treated comprehensively. Congenital cataract may cause deprivation amblyopia, refractive amblyopia, and permanent vision impairment. Early diagnosis and quick treatment, such as surgical timing and visual rehabilitation, are critical to perform successful management. Comprehensive care is required to monitor the visual result of cataract surgery.